2011
DOI: 10.1111/j.1750-3841.2011.02505.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Composition and Antioxidant Capacity of Commercially Available Blueberry and Blackberry Wines in Illinois

Abstract: The majority of wines are produced from grapes, but wine can also be produced from other fruits including blueberries and blackberries, which contain phenolic compounds that may contribute to human health. A comparative evaluation was conducted on commercial nongrape fruit wines and parameters related to their health benefits. Fruit wines made from blueberries and blackberries may have potential health applications and therefore could contribute to the economy of the wine industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
40
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 36 publications
12
40
2
2
Order By: Relevance
“…Unlike the total phenolic content, comparative studies of total anthocyanins, and even the ones conducted on a particular fruit wine are very scarce and more focused on the composition of individual free anthocyanins. Nevertheless, our results on anthocyanin content were generally in accordance with (13,14,22,34,40) or higher than (18) the ones reported by other authors.…”
Section: Total Phenolics and Total Anthocyanins In Fruit Winessupporting
confidence: 81%
See 2 more Smart Citations
“…Unlike the total phenolic content, comparative studies of total anthocyanins, and even the ones conducted on a particular fruit wine are very scarce and more focused on the composition of individual free anthocyanins. Nevertheless, our results on anthocyanin content were generally in accordance with (13,14,22,34,40) or higher than (18) the ones reported by other authors.…”
Section: Total Phenolics and Total Anthocyanins In Fruit Winessupporting
confidence: 81%
“…Furthermore, blackberry wines have been more extensively studied than other fruit wines, especially in Croatia. Our results were slightly higher than 601-1400 mg/L reported by Arozarena et al (10) and Ortiz et al (12), as well as slightly lower than 2212 (1052-3621) mg/L as reported by Johnson and Gonzalez de Mejia (22). On the other hand, results were consistent with the average concentration and/or ranges obtained in 17 and 4 samples of commercial blackberry wines from Croatia, equal to 1548 (733-2698) mg/L (13) and 1697-2628 mg/L (14), respectively.…”
Section: Total Phenolics and Total Anthocyanins In Fruit Winescontrasting
confidence: 53%
See 1 more Smart Citation
“…The fi rst indicator of wine acidity is the pH value (Table 1), which ranged from 3.11 (CBW 5) to 3.56 (OBW 13) in the investigated blackberry wines. The obtained results are consistent with our previous research results [Amidžić Klarić et al, 2011a], as well as with the results reported by other authors [Johnson & Gonzalez Mejia, 2012;Gao et al, 2012]. The conventional wine group samples were slightly more acidic (mean value: 3.28) than the organic wine samples (mean value: 3.38), which was confi rmed by the results of total acidity determination by titration.…”
Section: Physico-chemical Quality Parameterssupporting
confidence: 83%
“…Ethanol is important for both fl avour and stability of wine. Johnson & Gonzalez de Mejia [2012] reported the ethanol percentage range from 9.5 to 12.4% (10.7% average) in investigated Illinois blackberry wines. The alcoholic strength of the tested Croatian blackberry wines ranged from 9.37% (CBW 2) to 14.78% (CBW 1) by volume (Table 1), and no statistically signifi cant difference in alcoholic strength between the two groups of the analysed samples was observed.…”
Section: Physico-chemical Quality Parametersmentioning
confidence: 99%